Transgenic Plants as Sensors of Environmental Pollution Genotoxicity - Kovalchuk, Igor (Molecular Diversity Preservation International (MDPI), 2008)
Rapid technological development is inevitably associated with many environmental problems which primarily include pollution of soil, water and air. In many cases, the presence of contamination is difficult to assess. It is even more difficult to evaluate its potential danger to the environment and humans. Despite the existence of several whole organism-based and cell-based models of sensing pollution and evaluation of toxicity and mutagenicity, there is no ideal system that allows one to make a quick and cheap assessment. In this respect, transgenic organisms that can be intentionally altered to be more sensitive to particular pollutants are especially promising. Transgenic plants represent an ideal system, since they can be grown at the site of pollution or potentially dangerous sites. Plants are ethically more acceptable and esthetically more appealing than animals as sensors of environmental pollution. In this review, we will discuss various transgenic plant-based models that have been successfully used for biomonitoring genotoxic pollutants. We will also discuss the benefits and potential drawbacks of these systems and describe some novel ideas for the future generation of efficient transgenic phytosensors.